The Error Analysis Of Junior High School Students Based On Newman Procedure In Solving Numeration Problems Reviewing From Independent Learning: Error Analysis Of Junior High School Students Based On Newman Procedure In Solving Numeration Problems Reviewing From Independent Learning - Diki Mulyana; Eka Nurjanah; Wiwit Damayanti Lestari (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The points of this review (1) are to figure out the most missteps made by understudies in settling the base ability evaluation numeracy questions, and (2) to figure out the elements that make understudies commit errors in addressing the base skill appraisal numeracy questions because of free learning, (3) to depict the mistakes. what understudies do is botches made by understudies with autonomous learning in taking care of AKM numeracy issues. In this study utilizing an illustrative strategy with a subjective methodology, the subjects in this study were educators and understudies. Information assortment methods utilized tests, meetings, surveys, and documentation from the educator and 6 understudies in the classification of High, Medium, and Low. Test methods, interview procedures, survey strategies. The aftereffects of this study are (1) the slip-ups made by understudies in addressing the AKM numeracy questions in light of free picking up, as per the educator, incorporating absence of comprehension of the material, absence of comprehension of inquiries, and understanding inquiries. (2) The missteps made in tackling the inquiries that most understudies make are mistakes in perusing the inquiries, grasping the inquiries, and abilities during the time spent addressing the AKM numeracy questions. (3) Learning autonomy influences the consequences of addressing the AKM numeracy questions that are finished, understudies with high classifications on test results have high learning freedom, and understudies who get low experimental outcomes are less autonomous in learning.